2008
DOI: 10.1093/jxb/ern041
|View full text |Cite
|
Sign up to set email alerts
|

Phloem transdifferentiation from immature xylem cells during bark regeneration after girdling in Eucommia ulmoides Oliv

Abstract: Eucommia ulmoides Oliv. (Eucommiaceae), a traditional Chinese medicinal plant, was used to study phloem cell differentiation during bark regeneration after girdling on a large scale. Here it is shown that new sieve elements (SEs) appeared in the regenerated tissues before the formation of wound cambium during bark regeneration after girdling, and they could originate from the transdifferentiation of immature/differentiating axial xylem cells left on the trunk. Assays of water-cultured twigs revealed that girdl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 29 publications
6
54
0
1
Order By: Relevance
“…Calli culture sometimes induces ectopic formation of SE-like cells in several plant species (Wetmore and Rier, 1963;Aloni, 1980;reviewed in Sjolund, 1997). Regeneration of phloem tissues after bark girdling has also been used to study phloem differentiation (Pang et al, 2008). VISUAL has several advantages beyond these conventional methods.…”
Section: Discussion Visual Can Induce Ectopic Xylem and Phloem Se-likmentioning
confidence: 99%
“…Calli culture sometimes induces ectopic formation of SE-like cells in several plant species (Wetmore and Rier, 1963;Aloni, 1980;reviewed in Sjolund, 1997). Regeneration of phloem tissues after bark girdling has also been used to study phloem differentiation (Pang et al, 2008). VISUAL has several advantages beyond these conventional methods.…”
Section: Discussion Visual Can Induce Ectopic Xylem and Phloem Se-likmentioning
confidence: 99%
“…In general, for further analysis of the molecular mechanisms underlying cell differentiation processes, in vitro inducible systems are fruitful because of its high-synchronous differentiation (Fukuda, 1997;Roberts and McCann, 2000;McCurdy et al, 2008;Pang et al, 2008). One well-investigated system for in vitro xylem vessel element differentiation is the induction system using isolated mesophyll cells from Zinnia elegans (Fukuda, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…When APL is ectopically expressed throughout the vascular core, the protein represses xylem differentiation and induces phloem-like characteristics in the xylem tissue (Bonke et al, 2003; Carlsbecker and Helariutta, 2005). It has also been shown that immature xylem cells can transdifferentiate into phloem during bark regeneration in trees (Pang et al, 2008). Given the interplay between phloem and xylem differentiation (Carlsbecker and Helariutta, 2005; Miyashima et al, 2013), it is tempting to speculate that intermediates between both vascular identities could arise, leading to rapid diversity in both structure and physiology.…”
Section: Phloem Heterogeneity In Monocotsmentioning
confidence: 99%